Risk of a permanent work-related disability pension after incident venous thromboembolism in Denmark: A population-based cohort study. - Helle Jørgensen (Public Library of Science (PLoS), 2021)
Background Long-term complications of venous thromboembolism (VTE) hamper physical function and impair quality of life; still, it remains unclear whether VTE is associated with risk of permanent work-related disability. We aimed to assess the association between VTE and the risk of receiving a permanent work-related disability pension and to assess whether this association was explained by comorbidities such as cancer and arterial cardiovascular disease. Methods and findings A Danish nationwide population-based cohort study consisting of 43,769 individuals aged 25 to 66 years with incident VTE during 1995 to 2016 and 218,845 birth year-, sex-, and calendar year-matched individuals from the general population, among whom 45.9% (N = 120,540) were women, was established using Danish national registries. The cohorts were followed throughout 2016, with permanent work-related disability pension as the outcome. Hazard ratios (HRs) with 95% confidence intervals (CIs) for disability pension were computed and stratified by sex and age groups (25 to 34, 35 to 44, 45 to 54, and 55 to 66 years of age) and adjusted for comorbidities and socioeconomic variables. Permanent work-related disability pensions were granted to 4,415 individuals with VTE and 9,237 comparison cohort members (incidence rates = 17.8 and 6.2 per 1,000 person-years, respectively). VTE was associated with a 3-fold (HR 3.0, 95% CI: 2.8 to 3.1) higher risk of receiving a disability pension. Adjustments for socioeconomic status and comorbidities such as cancer and cardiovascular diseases reduced the estimate (HR 2.3, 95% CI: 2.2 to 2.4). The risk of disability pension receipt was slightly higher in men than in women (HR 2.5, 95% CI: 2.3 to 2.6 versus HR 2.1, 95% CI: 2.0 to 2.3). As this study is based on medical and administrative registers, information on post-VTE care, individual health behavior, and workplace factors linked to disability pension in the general population are lacking. Furthermore, as disability pension schemes vary, our results might not be directly generalizable to other countries or time periods. Conclusions In this study, incident VTE was associated with increased risk of subsequent permanent work-related disability, and this association was still observed after accounting for comorbidities such as cancer and cardiovascular diseases. Our results emphasize the social consequences of VTE and may help occupational and healthcare professionals to identify vulnerable individuals at risk of permanent exclusion from the labor market after a VTE event.